2021
DOI: 10.3390/su131910971
|View full text |Cite
|
Sign up to set email alerts
|

Green Supply Chain Management and Its Impact on Consumer Purchase Decision as a Marketing Strategy: Applying the Theory of Planned Behavior

Abstract: This study examines the impact of green supply chain management (GSCM) on consumers environmentally friendly purchase behavior. We surveyed 283 consumers and analyzed the data using SPSS 18.0, AMOS 18.0, and verified them with structural equation modeling. To support the primary data analysis results, we conducted focus group interviews (FGIs) of 16 consumers. According to the primary data analysis, consumers’ subjective norms and perceived behavioral control positively influence GSCM. However, attitude did no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 34 publications
1
17
0
1
Order By: Relevance
“…Zhu et al [34] came up with a GSCM with five factors including internal environmental management, green purchasing, cooperation with customers, eco-design, and investment recovery by utilizing materials and equipment efficiently [35]. Lee et al [36] and Zaid et al [37] perceived GSCM to include two dimensions composed of internal GSCM management and external GSCM management. Internal GSCM management is relevant in meeting internal environmental targets under management supports utilizing the internal system and processes.…”
Section: Green Supply Chain Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…Zhu et al [34] came up with a GSCM with five factors including internal environmental management, green purchasing, cooperation with customers, eco-design, and investment recovery by utilizing materials and equipment efficiently [35]. Lee et al [36] and Zaid et al [37] perceived GSCM to include two dimensions composed of internal GSCM management and external GSCM management. Internal GSCM management is relevant in meeting internal environmental targets under management supports utilizing the internal system and processes.…”
Section: Green Supply Chain Managementmentioning
confidence: 99%
“…External GSCM management goes beyond the boundary of the corporate umbrella into the upstream and downstream of the supply chain. Lee et al [36] named internal environmental management and eco-design as two internal practices, and green purchasing and cooperation with customers as external practices. Zaid et al [37] categorize GSCM into internal GSCM and external GSCM.…”
Section: Green Supply Chain Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…e launch of each unit of product is the construction scale, and each waste is ensured to be optimally processed. After meeting the data and information on market recycling, each unit of waste is processed, and the conversion rate of each link becomes 100% [23,24]. en the market demand function is expressed as D � Q − αP 1 1 , α > 0; among them, Q represents the product market capacity and P 1 1 represents the unit product sales price; the waste recycling expression is V � g + μP 2 , μ > 0, P2 represents the unit waste recycling price, and g represents the amount of the waste that the consumer voluntarily returns when the waste recycling price of the unit is 0.…”
Section: Government Rewards and Punishmentsmentioning
confidence: 99%
“…Kannan, (2021) reported that SP can only be achieved if there is strong government pressure and availability of rules and regulations. Lee et al (2021) also reported that many organizations are adopting the green practice only to comply with government regulations. In our study, 18 of the participants noted that they complied with SP practices because of pressure from the government:…”
Section: Resultsmentioning
confidence: 99%